Sosialisasi Dampak Dan Pengaruh Media Sosial Di SMA Pasundan 1 Cimahi - Wowo Trianto; Intan Pujilestari; Rizqy Dimas Monica; Edih Gunawan; Ayu Hendrati Rahayu; Lusi Marlina (JPPkM: Jurnal Pengabdian dan Pemberdayaan kepada Masyarakat, 2026)
The digital era has brought major changes in social interaction patterns, especially for Generation Z who rely heavily on social media platforms in their daily lives. As a group that grew up alongside technology, teenagers are often exposed to all kinds of content without proper filters The implementation of this community service program aims to introduce the impact and influence of social media at SMA Pasundan 1 Cimahi. The program focuses on educating about the influence of social media on Gen Z's mindset, how to filter information (anti-hoaxes), communication ethics in the digital world, and time management (screen time) to maintain focus and mental health. The implementation methods include preparation, material development, and socialization. The results show that the program was successfully carried out, with participants showing high enthusiasm. Participants were able to understand how to use social media and practice communication ethics online, thereby supporting the mindset of Gen Z.